2012
DOI: 10.1016/j.theriogenology.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural peculiarities associated with multiflagellate sperm in the emu, Dromaius novaehollandiae

Abstract: Multiflagellate sperm represent a rare defect in mammals and also in the emu where an incidence of only 1% multiflagellate sperm was recorded in semen samples from 15 birds. Biflagellate sperm were the most frequent form of the defect observed, but 3-to 5-tailed sperm were also noted. An association was apparent between multiple tails and macrocephalic sperm which accounted for 0.6% of multiflagellate sperm. Structural features of the defect were generally similar to those seen in mammals. The duplicated tails… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…This study however demonstrated that the characteristic filiform shape of emu sperm was particularly amenable to the use of phase contrast microscopy with glutaraldehyde-fixed and Wright's-stained smears. Examining stained smears with phase contrast microscopy proved to be a rapid and convenient method for clearly distinguishing the various components of emu sperm and also clearly discriminated between normal and abnormal gametes in this species [41][42][43][44].…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This study however demonstrated that the characteristic filiform shape of emu sperm was particularly amenable to the use of phase contrast microscopy with glutaraldehyde-fixed and Wright's-stained smears. Examining stained smears with phase contrast microscopy proved to be a rapid and convenient method for clearly distinguishing the various components of emu sperm and also clearly discriminated between normal and abnormal gametes in this species [41][42][43][44].…”
Section: Techniquementioning
confidence: 99%
“…Recent detailed publications on the classification and description of defective sperm in the emu [41][42][43][44] have emphasized the need to re-evaluate the dearth of published information on normal emu sperm, particularly at the LM level. This information is required to provide comparative data for the accurate identification of abnormal forms.…”
mentioning
confidence: 99%
“…This relatively rare condition may adversely influences sperm motility and therefore fertility (Barth and Oko, 1989;Escalier, 1983;Nistal et al, 1977). The ultrastructural features of this defect have been thoroughly described, demonstrating a degree of uniformity acrossvarious mammalian species (Barth and Oko 1989;Brito, 2007;Brito et al, 2010;Escalier 1983;Nistal et al, 1977), and non-passerine birds (see Du Plessis and Soley, 2012b). The neck region of affected sperm reveal two or more apparently morphologically normal centriolar complexes (Fig.…”
Section: Structural Anomalies Associated With the Centriolar Complexmentioning
confidence: 88%
“…5). Unlike the situation in mammals where the broad nuclear base generally provides enough space for the implantation of multiple CC"s, in bird sperm of normal dimensions the narrow, cylindrical head base displays tenuous peripheral widening in order to accommodate the additional diplosomes (Du Plessis and Soley, 2012b). In multiple tailed human sperm, the axonemal complexes often appear to be defective (Escalier, 1983;Nistal et al, 1977) as also sometimes observed in the cane rat (see Fig.…”
Section: Structural Anomalies Associated With the Centriolar Complexmentioning
confidence: 97%
“…Monoflagellate spermatozoa are the most frequently found type among teleosts, described for species with internal fertilization and external fertilization [6,10]. The presence of biflagellate spermatozoa is widespread in the animal kingdom from flatworms to mammals [5,11]; however, in fishes, the biflagellate condition seems to be less frequent and has only been described for over 16 families from seven orders [10].…”
Section: Introductionmentioning
confidence: 99%